Teachers as experimenter and behavioral engineers: An extension and cross-cultural replication - Bauermeister, Jose J.; Jemail, Jay Ann (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present study reports three of the experiments that were conducted by elementary school teachers in Puerto Rico during an in-service training in the systematic application of behavior principles in the classroom setting. Experiments 1 and 2 demonstrated the modification of non-completion of written assignments and out-of-seat behaviors, respectively, using a reversal design. In experiment 3 a multiple baseline design was employed to illustrate the modification of non-completion of written assignments and the quality (neatness) of written work. These findings supported the reliability, generality, and applicability of the behavior analysis principles. The contribution of trained behavioral engineers for community psychology and the prevention model of psychological services is discussed. The findings of the present study are relevant to Latin American countries and/or communities where the shortage of professionals trained in the behavioral sciences is a critical problem.